Monetary overhang and the dynamics of prices, exchange rates, and income in the transition to a market economy - Bert Hofman; Michael J. Koop (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
The long road from capitalism to capitalism the Eastern European economies have made has been paved with many economic problems, but the transition from a command economy into a market economy is likely to become a bumpy ride as well. Apart from the major real economic reforms that have to take place, combined with virtual turnaround of the political structure, several countries aiming to reform face a monetary problem as well. Due to persistent state budget deficits, financed by the printing press, a so called monetary overhang threatens the reform process. Monetary overhang is here defined as the excess of money supply over demand at the current price level and at world market interest rates. The consequences of the monetary overhang under a planning system are obvious: the fixity of prices prevents the real money supply from falling to its equilibrium level, and the situation of repressed inflation translates into long queues in front of shops, forced savings, and, if not checked, into a flourishing black market and corruption. The official exchange rate is overvalued, but import demand is checked by rationing of foreign exchange.
Keywords: 330; Marktwirtschaft; Wirtschaftsreform; Geldmenge; Preis; Wechselkurs; Einkommen; Theorie